Inferior Epigastric Artery Pseudoaneurysm in a Kidney Transplant Recipient - M. Tozzi; B. Molteni; M. Franchin; G. Ietto; G. Soldini; V. Bertocchi; G. Carcano (Case Reports in Transplantation)
Pseudoaneurysm of inferior epigastric artery (IEA) is a very rare clinical entity. We reported a case of combined kidney transplant and pseudoaneurysmectomy in a young HBV-HCV-HIV recipient. This case emphasizes the possibility of planning a safe and correct surgical treatment and the best timing to treat IEA pseudoaneurysm. An exhaustive preoperative radiological study in all patients candidate to kidney transplant could identify the possible aortoiliac disease both stenotic or dilatative even if it is rare and helps to define the best treatment options.